The Application of Critical Path Method (CPM) in The Development of Project Management Information Systems Using the Incremental Model (Case Study: CV. Panca Pilar Kota Madiun) - Hamim Tohari; RB. Iwan Suhasto (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2023)
Good control is needed in managing a project, starting from controlling the human resources to systematic scheduling. CV. Panca Pilar Madiun is a contractor service company, that does not yet have an information system that can be used as a control tool in project management. Critical Path Method (CPM) is one method that can be used to schedule projects. This study aims to design a project management information system by implementing CPM. The system design is done using the Incremental Model. The results of this study are in the form of a prototype system that fits the needs of CV. Panca Pilar Madiun, includes system flow, Contextual Data Model(CDM), and User Interface(UI).